In 18F-positron emission tomography/computed tomography-guided precision radiotherapy for centrally located non-small cell lung cancer, tumor related atelectasis is a prognostic factor of survival - Wang, Nan; Qiao, Yun; Song, Yingqiu; Wang, Zheng; Li, Xia; Liu, Chengsen; Wang, Ye; Wu, Yu; He, Rong; Wang, Chenyu; Ren, Yangwu; Li, Guang; et al. (Frontiers in Oncology, 2022)
Purpose Tumor related atelectasis(TRA) is an essential factor affecting survival that can cause chest pain, cough, hemoptysis, chest tightness, dyspnea, and even death. In the current study, we explored the possible impact of TRA on survival in cancer patients and the guiding significance of 18F-positron emission tomography/computed(PET/CT) in radiotherapy for patients with atelectasis tumors. Methods In this retrospective study，we analyzed the treatment model and survival of patients with centrally located non-small cell lung cancer(NSCLC) treated with radiotherapy at two medical centers between May 2005 and August 2019. We identified 152 eligible patients and used propensity score matching (1:1) to process the data to reduce confounding factors, data bias, and mal-distribution. Results We used propensity scores created well-matched groups of 57 patients overall with or without TRA. The one-year survival rate of all patients was 71.9%, and the two-year survival rate was 33.3%. Compared to the atelectasis group, the overall survival (OS) of patients in the non-atelectasis group was significantly prolonged (25 months vs. 17 months, p = 0.004), as well as in the atelectasis recovery group (28 months vs. 14 months, p = 0.008). In multivariate analysis, non-atelectasis was closely correlated with favorable OS (HR, 1.804 (−2.840); 95% CI, 1.145–2.840; p = 0.011). Conclusion PET/CT can accurately stage NSCLC and better guide the treatment of NSCLC complicated with atelectasis. Tumor-associated atelectasis in patients with centrally located NSCLC can lead to is a poor prognostic marker. Keywords: Central Non-small cell lung cancer; tumor-associated atelectasis; prognostic factors